(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article describes various theories of practical application of the knowledge, skills, and abilities of the teacher as a result of the professional activity of the teacher in the pedagogical activity, as a result of the professional activity of the teacher and the personal skills.